The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00705-017-3684-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of ribavirin in the treatment of hepatitis C virus-associated mixed cryoglobulinemia with interferon-free regimens

Abstract: Mixed cryoglobulinemia (MC) is the most common extrahepatic manifestation of chronic hepatitis C (CHC), with the presence of symptoms in 10-15% of cases. There have been encouraging data regarding immunological and clinical responses in patients treated with the novel combinations of direct-acting antivirals (DAAs), but the role of ribavirin (RBV) in the treatment of MC has not yet been demonstrated. We prospectively enrolled 132 patients affected by MC and CHC, and virological, immunological and clinical resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…11 Our findings revealed significantly higher RF with significantly lower C3 and C4 serum levels among the included HCV-MC in comparison with the controls, with significant improvements in their level following DAAs. In line with our data, Boglione et al 14 and Gragnani et al 37 reported similar findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…11 Our findings revealed significantly higher RF with significantly lower C3 and C4 serum levels among the included HCV-MC in comparison with the controls, with significant improvements in their level following DAAs. In line with our data, Boglione et al 14 and Gragnani et al 37 reported similar findings.…”
Section: Discussionsupporting
confidence: 93%
“…Before the advent of direct-acting antivirals (DAAs), interferon (IFN)-based regimens produced clinical recovery with subsequent improvement of MC as a result of HCV clearance; however, the side effects of IFN may mimic the MC manifestations, and the relapse rate with IFN-based regimens was high. 13 Boglione et al 14 reported a study on the treatment of HCV-MC with IFN-free regimens, with or without ribavirin, and concluded that IFN-free regimens were effective and well tolerated in treating HCV-MC and significantly promoted a decrease in cryoglobulins.…”
Section: Introductionmentioning
confidence: 99%